2015
DOI: 10.1074/jbc.m114.573956
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction of CaVβ with Actin Up-regulates L-type Calcium Currents in HL-1 Cardiomyocytes

Abstract: Background: Enhancement of L-type calcium channel trafficking by ␤-subunits (Ca V ␤) remains unclear. Results: Ca V ␤ associates directly with actin filaments. In cardiomyocytes, overexpression of Ca V ␤ 2 stimulates L-type currents without altering their voltage dependence of activation. Actin cytoskeleton disruption inhibited channel up-regulation. Conclusion: Ca V ␤ anchors the channel to actin filaments for plasma membrane delivery. Significance: Novel insights into L-type channel anterograde trafficking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 50 publications
3
52
0
Order By: Relevance
“…Properties of I f current in HL-1 cells are similar to those in SANC; inhibition of I f current in HL-1 cells as in SANC significantly suppresses diastolic depolarization and reduces automaticity. L-type and T-type Ca channels, inward rectifier K + channels, and Stim1 are also expressed in HL-1 cells [2528]. The effects of application of thapsigargin and ryanodine to HL-1 cells as well as effects of PKA activation are the same as in SANC.…”
Section: Resultsmentioning
confidence: 99%
“…Properties of I f current in HL-1 cells are similar to those in SANC; inhibition of I f current in HL-1 cells as in SANC significantly suppresses diastolic depolarization and reduces automaticity. L-type and T-type Ca channels, inward rectifier K + channels, and Stim1 are also expressed in HL-1 cells [2528]. The effects of application of thapsigargin and ryanodine to HL-1 cells as well as effects of PKA activation are the same as in SANC.…”
Section: Resultsmentioning
confidence: 99%
“…Could the disruption of F-actin be responsible for the spatial disorganization of the Ca V 1.3 Ca 2+ channels? It has been suggested that a direct association between Ca V β 2 and F-actin promotes the directional transport of Ca 2+ channels to the plasma membrane of cardiomyocytes (34), and, at the ribbon synapse of salamander photoreceptors, the confinement of Ca 2+ channels beneath the ribbon is regulated by actin and membrane cholesterol (35). The disruption of F-actin with latrunculin-A in WT IHCs has been shown to disrupt the spatial distribution of Ca V 1.3 Ca 2+ channels (23) in a manner similar to that observed here, in the active zones of IHCs lacking clarin-1 from the 2 types of mutant mice.…”
Section: Hearing Rescue By Virus-mediated Gene Transfer Into the Ihcsmentioning
confidence: 99%
“…In fact, in the presence of cytochalasin D, which disrupts actin polymerization, over-expression of Ca v β 2 failed to stimulate L-type currents, as is observed in cells with intact actin cytoskeleton. Together, these findings highlight the importance of Ca v β for the surface expression of VGCC and point to a possible mechanism in which Ca v β promote the transport of the channel to the plasma membrane via its interaction with actin (Table 3) [102]. For several decades, the described functions of Ca v β have been exclusively linked to VGCC.…”
Section: Actin the Most Recently Identified Partner Of Ca V βmentioning
confidence: 95%
“…In their recent study, Stölting et al [102] uncovered a direct interaction between Ca v β 2 and actin filaments. The interaction was demonstrated in vitro as well as in vivo, it involves both, the SH3 and GK domains, suggesting that binding to actin is a property shared by all Ca v βs.…”
Section: Actin the Most Recently Identified Partner Of Ca V βmentioning
confidence: 97%
See 1 more Smart Citation